Tumour-associated macrophages - De Palma, Michele; Squadrito, Mario (Henry Stewart Talks, 2012)
The correlation between Tumor Associated Macrophage (TAM) infiltration and tumor progression in cancer patients, Evidence for a protumoral function of TAMs in mouse tumor models, Hallmark features of TAMs enable tumor progression, Promotion of inflammation, Chronic inflammatory diseases and cancer risk, Promotion of matrix remodeling, Promotion of tumor cell invasion, Promotion of metastasis, Promotion of angiogenesis, TAM heterogeneity in tumors, Identification and characterization of TAM subsets in mouse tumor models, TIE2-expressing macrophages and inflammatory TAMs, Origins of TAM subsets: Distinct hypothesis, Tumor responses to anticancer therapies: Role of TAMs, Reprogramming TAMs from a pro- to an anti-tumoral function, Deciphering TAM heterogeneity in human cancer, Complexity of leukocyte infiltrates in human cancer